2006
DOI: 10.1104/pp.106.081885
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Clock Regulation of Starch Metabolism Establishes GBSSI as a Major Contributor to Amylopectin Synthesis in Chlamydomonas reinhardtii  

Abstract: Chlamydomonas reinhardtii displays a diurnal rhythm of starch content that peaks in the middle of the night phase if the algae are provided with acetate and CO 2 as a carbon source. We show that this rhythm is controlled by the circadian clock and is tightly correlated to ADP-glucose pyrophosphorylase activity. Persistence of this rhythm depends on the presence of either soluble starch synthase III or granule-bound starch synthase I (GBSSI). We show that both enzymes play a similar function in synthesizing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
117
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(123 citation statements)
references
References 58 publications
5
117
0
1
Order By: Relevance
“…Alternatively, the wx b GBSS protein still might be capable of synthesizing amylopectin within starch granules, but not amylose. It has been previously shown that GBSS has the ability to synthesize or extend both types of starch polymers (Delrue et al 1992;Denyer et al 1996;Ral et al 2006). In maize, GBSS activity in isolated starch granules did not strongly correlate with amylose content (Tsai 1974), which suggests that there are other factors that influence amylose content in starch granules in addition to GBSS.…”
Section: Discussionmentioning
confidence: 78%
“…Alternatively, the wx b GBSS protein still might be capable of synthesizing amylopectin within starch granules, but not amylose. It has been previously shown that GBSS has the ability to synthesize or extend both types of starch polymers (Delrue et al 1992;Denyer et al 1996;Ral et al 2006). In maize, GBSS activity in isolated starch granules did not strongly correlate with amylose content (Tsai 1974), which suggests that there are other factors that influence amylose content in starch granules in addition to GBSS.…”
Section: Discussionmentioning
confidence: 78%
“…Although this decrease in the starch content compared to the wild type is not explained at the moment, this could be due to subtle differences in transcriptional regulation of the complementing transgene by comparison to the wild-type gene. Indeed, transcription of STA6 is known to be under circadian clock control and exerts a tight control in the carbon flux to starch (Zabawinski et al, 2001;Ral et al, 2006). Limitations in the indirect pathway more likely rely on enzymatic steps involved from starch breakdown to nonphotochemical reduction of PQs.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorophyll a plus b concentration was determined with a l 20 spectrophotometer (Perkin Elmer). Starch was extracted according to Ral et al (2006). Starch amounts were determined spectrophotometrically using the Starch Kit (Roche, R-Biopharm).…”
Section: Chlorophyll and Starch Contentsmentioning
confidence: 99%